Do not underestimate anterior prostate cancer - Kudláčková, Šárka; Kurfürstová, Daniela; Král, Milan; Hruška, František; Vidlář, Aleš; Študent, Vladimír (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2021)
AIMS: With the introduction of magnetic resonance imaging in the diagnosis of prostate cancer and its use in targeted prostate biopsy, an increased incidence of anterior-predominant prostate cancer (APC) has been observed. METHODS: We enrolled 200 patients who underwent radical prostatectomy at our department between 12/2017 and 04/2019. We evaluated tumour location in the individual segments of the prostate, index tumour location and volume, and compared the postoperative stage, Gleason score, grade group (GG), and the presence of extraprostatic extension (EPE) in APC and posterior prostate cancer (PPC). We assessed the rate of MRI scans prior to prostate surgery as well as the influence of family history and PSA on the presence of APC. RESULTS: We found a significantly higher rate of anterior tumours than previously reported (37%) and confirmed that these tumours are diagnosed with a significantly larger index tumour volume (P=0.003). We also showed that a mere 6.76% of APCs were low-risk tumours not requiring radical treatment. Furthermore, anterior tumours were found significantly more often (P=0.001) in patients who underwent preoperative MRI. No differences were observed between PSA values, family history, presence of EPE, or locally advanced disease in APC vs. PPC. CONCLUSIONS: The frequency of anterior tumours is higher than previously thought, and they include tumours requiring radical treatment. When these tumours are neglected, it may lead to patient undertreatment with impact on their life prognosis. Thus, we consider the use of MRI-targeted prostate biopsy to be a necessity both for ruling out APC in the case of repeatedly negative prostate biopsies and, in particular, before patient inclusion in active surveillance.
Keywords: prostatektomie; prostatický specifický antigen; nádory prostaty; lidé; Prostate; Neoplasm Grading; Humans; Prostatic Neoplasms; Prostate-Specific Antigen; Male; mužské pohlaví; Prostatectomy; prostata; stupeň nádoru